PENINGKATAN KETERAMPILAN BERBICARA BAHASA ARAB MURID MDTA IRSYADUL IBAD MELALUI PELATIHAN MUHADATSAH - anwar, syahrul; munir, dede; septiadi, yans (Universitas Negeri Malang, 2023)
Learning Arabic, especially learning speaking skills (Speaking/Muhadatsah), which is applied to Majlis Al Hidayah students tends to be difficult and boring, so this has an impact on the slow development of students' Arabic speaking skills (Speaking/Muhadatsah). Therefore, it is necessary to have interesting and effective methods in teaching, one of which is creating dialogues that are often used by students. There are several steps in implementing the muhadatsah method, namely: Preparing dialogue material and determining the topic that will be presented in writing. Muhadatsah material should be adjusted. with the level of development and abilities of students, and using teaching aids as aids for muhadatsah. Because the presence of teaching aids can explain children's perceptions of the meaning and intent contained in muhadatsah. Apart from that, it can attract students' attention and not be boring. The KPM (Community Service Lecture) program aims to provide training to students at the Majlis Al Hidayah institution to improve Arabic speaking skills through the application of the muhadatsah method, which is expected to improve learning outcomes for students who are very hampered by the ability to memorize vocabulary and new sentence. The result of PKM is an increase in Arabic language skills at MDTA Irsyadul Ibad.